The low overpotential regime of acidic water oxidation part II: trends in metal and oxygen stability numbers. Issue 5 (31st March 2022) - Scott, Soren B.; Sørensen, Jakob E.; Rao, Reshma R.; Moon, Choongman; Kibsgaard, Jakob; Shao-Horn, Yang; Chorkendorff, Ib
Abstract : The relationship between metal dissolution and lattice oxygen evolution is mapped out for water oxidation in acidic electrolyte. Abstract : The operating conditions of low pH and high potential at the anodes of polymer electrolyte membrane electrolysers restrict the choice of catalysts for the oxygen evolution reaction (OER) to oxides based on the rare metals iridium or ruthenium. In this work, we investigate the stability of both the metal atoms and, by quantitative and highly sensitive 18 O isotope labelling experiments, the oxygen atoms in a series of RuO x and IrO x electrocatalysts during the OER in the mechanistically interesting low overpotential regime. We show that materials based on RuO x have a higher dissolution rate than the rate of incorporation of labelled oxygen from the catalyst into the O2 evolved ("labelled OER"), while for IrO x -based catalysts the two rates are comparable. On amorphous RuO x, metal dissolution and labelled OER are found to have distinct Tafel slopes. These observations together lead us to a full mechanistic picture in which dissolution and labelled OER are side processes to the main electrocatalytic cycle. We emphasize the importance of quantitative analysis and point out that since less than 0.2% of evolved oxygen contains an oxygen atom originating from the catalyst itself, lattice oxygen evolution is at most a negligible contribution to overall OER activity for RuO x and IrO x in acidic electrolyte.